2003
DOI: 10.1046/j.1460-9592.2003.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative anxiety and postoperative behavioural disturbances in children undergoing intravenous or inhalation induction of anaesthesia

Abstract: Although children were more anxious during i.v. induction than inhalation induction, there was no difference in the incidence of behavioural disturbances in the first 2 weeks postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 27 publications
2
34
0
5
Order By: Relevance
“…Franz (2004) found that children aged between 4 and 12 years who underwent an inhalation induction had greater medical fears in the post-operative period compared with those who had an IV induction. However, Aguilera et al (2003) found that a greater number of the children (aged 2-14 years) in their study displayed anxious behaviour during an IV induction compared to an inhalation induction. It would therefore, also be of use to determine which type of anaesthesia holds the least possibility of increasing anxiety in the peri-operative period.…”
Section: Introductionmentioning
confidence: 68%
“…Franz (2004) found that children aged between 4 and 12 years who underwent an inhalation induction had greater medical fears in the post-operative period compared with those who had an IV induction. However, Aguilera et al (2003) found that a greater number of the children (aged 2-14 years) in their study displayed anxious behaviour during an IV induction compared to an inhalation induction. It would therefore, also be of use to determine which type of anaesthesia holds the least possibility of increasing anxiety in the peri-operative period.…”
Section: Introductionmentioning
confidence: 68%
“…Midazolam premedication can prolong recovery time, but it can also lessen the postoperative agitation caused by sevoflurane. 40 Midazolam cannot be suitable for all patients, therefore a detailed analysis and evaluation of the use of this agent would be welcome.…”
Section: Discussionmentioning
confidence: 99%
“…Unter Verwendung von Midazolam und "eutectic mixture of local anesthetic" (EMLA) hatten nur 10 % der Kinder Angst bei der Maskeneinleitung, 46 % hingegen, wenn versucht wurde, zuerst eine Vene zu punktieren [3]. Alte Daten, nach denen eine inhalative Einleitung mehr postoperative VerhaltensverĂ€nde-rungen bewirkt als eine intravenöse, beruhen nicht auf einer heute fĂŒr gut befundenen anĂ€sthesiologischen Praxis.…”
Section: Inhalative Narkoseeinleitungunclassified